Strategi Komunikasi Humas DJKI Kemenkumham dalam Membangun Media Relations dengan Jurnalis: Studi pada Humas DJKI Kemenkumham & SCTV - Ikhvani Audina, Cut (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The role of mass media is crucial in shaping public opinion and disseminating information to the broader community. A harmonious relationship between organizations and the media, particularly through public relations, is essential for conveying a positive image and maintaining public trust. This study focuses on the role of the Public Relations Office of the Direktorat Jenderal Kekayaan Intelektual (DJKI) of the Ministry of Law and Human Rights (Kemenkumham) in building media relations with journalists, with a specific focus on journalists from SCTV. The study aims to identify the communication strategies employed by the DJKI’s Public Relations Office and evaluate the effectiveness and challenges faced in their interactions with the media. A qualitative research approach was used, including in-depth interviews and document analysis to gain insights from both DJKI’s PR officials and SCTV journalists. The findings indicate that the DJKI’s Public Relations Office employs various strategies to build and maintain positive relationships with journalists. These strategies include organizing press conferences, distributing press releases, and managing social media. However, the study also identifies several challenges, such as differences in response times, information gaps, and differing expectations between the PR team and journalists. The insights from this research provide valuable information for the DJKI’s Public Relations Office and other PR practitioners on effective media management. The recommendations are expected to enhance communication strategies and strengthen media relationships, ultimately helping to achieve institutional communication goals and improve public image.